Monocrystalline silicon special-shaped net-shaped suede structure, texturing additive, texturing liquid and preparation method
By adopting a single crystal silicon special-shaped mesh suede structure in HJT batteries, the adhesion of low-temperature conductive silver paste is enhanced, the problem of insufficient adhesion of silver paste is solved, the photoelectric conversion efficiency of the battery is improved and the cost is reduced.
Patent Information
- Application Number
- CN202411538161.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
The adhesion of low-temperature conductive silver paste on the surface of the single crystal silicon pyramid in HJT batteries is insufficient, resulting in poor contact between the silver paste and the pyramid, affecting the photoelectric conversion efficiency of the battery.
Using a single crystal silicon special-shaped meshed silk structure, the adhesion of the low-temperature conductive silver paste is enhanced by preparing a pyramid with a mesh structure with microplane intersecting. This structure is prepared by velvet-making additives, velvet-making liquid and preparation methods, including anionic surfactants, nonionic surfactants, plant polysaccharide compounds, nucleating agents, dispersants and other components.
The adhesion of low-temperature conductive silver paste on the suede is improved, the contact between the silver paste and the substrate is enhanced, the photoelectric conversion efficiency of HJT batteries is improved, and the amount of conductive silver paste is reduced, achieving the cost reduction effect.
Smart Images

Figure CN119392381A_ABST
Abstract
Description
Technical Field
[0001] The invention mainly relates to the field of solar cell manufacturing, and in particular to a single crystal silicon special-shaped mesh velvet surface structure, a velvet-making additive, a velvet-making liquid and a preparation method. Background Art
[0002] With the continuous advancement of photovoltaic cell technology, the photovoltaic industry has started the trend of iteration from P-type to N-type, moving towards a higher efficiency level. N-type technology routes represented by TOPCon (Tunnel Oxide Passivating Contacts) tunnel oxide passivation contact cells and HJT (Heterojunction with Intrinsic Thin-film) heterojunction cells have made breakthroughs one after another, and the industrialization process is expected to accelerate. In addition, the next generation of perovskite stacked cells such as perovskite and TOPcon stacking, perovskite and HJT stacking are in the ascendant, and various preparation processes are emerging in an endless stream. Although HJT cells and perovskite / HJT stacked cells are currently highly efficient, they have not been widely deployed due to cost factors. Therefore, it is urgent to further improve the power generation efficiency and reduce the unit watt cost of HJT cells. Among them, the efficiency of HJT cells is greatly affected by the matching of low-temperature conductive silver paste and process. This is because the adhesion of low-temperature conductive silver paste on the silicon substrate is poor, resulting in poor contact between the silver paste and the pyramid. Therefore, it is of great significance to improve the adhesion of low-temperature conductive silver paste on the monocrystalline silicon pyramid. As we all know, the texturing process is indispensable in the preparation of HJT batteries. Therefore, the adhesion of low-temperature conductive silver paste on the pyramids can be improved by controlling the different pyramid morphologies after texturing, thereby improving the contact between the silver paste and the substrate, so as to achieve the effect of improving the photoelectric conversion efficiency of HJT batteries.
[0003] At present, the pyramid surfaces of HJT batteries after texturing are very smooth and have no microstructure, especially after the CP (Chemical Polishing) process, the pyramid surfaces are even smoother, which makes it difficult for the low-temperature conductive silver paste to adhere to the surface of the pyramid, which is not conducive to the contact between the low-temperature conductive silver paste and the pyramid after sintering. Secondly, since the thickness of the amorphous silicon film plated on the HJT battery is very thin, it is required that the pyramid structure should not have a spire and the microstructure of the spire during texturing, so as to protect the amorphous silicon film to the greatest extent, thereby ensuring the efficiency of the battery. In addition, enhancing the adhesion of the low-temperature conductive silver paste to the velvet surface can also reduce the amount of conductive silver paste used, thereby achieving the effect of cost reduction. Therefore, there is an urgent need for a technical solution for a texturing additive that can prepare a microstructure on the surface of the pyramid to enhance the adhesion of the conductive silver paste on the pyramid while there is no microstructure on the spire of the pyramid. Summary of the invention
[0004] In order to improve the adhesion between silver paste and monocrystalline silicon velvet structure and reduce the amount of low-temperature conductive silver paste in HJT batteries, the present invention proposes a monocrystalline silicon special-shaped mesh velvet structure, a texturing additive and a texturing liquid for preparing the special-shaped mesh velvet structure, and a preparation method of the above-mentioned special-shaped mesh velvet structure. The edges and spires of the monocrystalline silicon special-shaped mesh velvet structure have no microstructures, are similar in size and uniform, can improve the uniformity of silver paste distribution, enhance the adhesion between silver paste and velvet structure, and reduce the amount of low-temperature silver paste. The texturing additive and texturing liquid can produce the above-mentioned monocrystalline silicon special-shaped mesh velvet structure under the premise of ensuring alcohol-free, environmentally friendly, and rapid texturing.
[0005] A single crystal silicon irregular mesh velvet structure comprises randomly distributed "pyramid" structures with a size of 1 to 4 μm; the top of the "pyramid" structure is smooth, the side of the "pyramid" is transitioned to the top by multiple ridges with different inclination angles, and the ridges are transitioned by multiple planes with different inclination angles; the tower surface is composed of multiple micro planes intersecting with each other, and when the "pyramid" structure is viewed from above, the tower surface of the "pyramid" has a mesh structure of micro planes intersecting in a mesh shape.
[0006] The texturing additive used for preparing the single crystal silicon special-shaped mesh velvet structure includes the following components calculated by weight: 0.1 to 1 part of anionic surfactant, 0.1 to 5 parts of nonionic surfactant, 0.05 to 1 part of plant polysaccharide compound, 0.1 to 5 parts of nucleating agent, 0.1 to 2 parts of dispersant, 1 to 2 parts of sodium hydroxide, 0.1 to 1 part of defoaming agent, and 60 to 80 parts of deionized water.
[0007] Furthermore, the anionic surfactant is one or more of linear alkylbenzene sulfonate (LAS), sodium α-olefin sulfonate (AOS), sodium alkyl sulfonate (SAS), sodium succinate sulfonate, and α-sulfo fatty acid methyl ester (mono) sodium salt (MES).
[0008] Furthermore, the nonionic surfactant is one or more of fatty alcohol polyoxyethylene ether (AEO), fatty acid polyoxyethylene ester, alkylphenol polyoxyethylene ether (APEO), Tween 60, and Tween 80.
[0009] Furthermore, the plant polysaccharide compound is one or more of Tremella polysaccharide, Lentinan, β-glucan, seaweed polysaccharide, carrageenan, and konjac glucomannan.
[0010] Furthermore, the nucleating agent is one or more of polyglutamic acid, polylactic acid, sodium hyaluronate, and xanthan gum.
[0011] Furthermore, the dispersant is one or more of sodium polyacrylate, ammonium polyacrylate, polydimethyldiallyl ammonium chloride (PDMDAAC), and maleic anhydride-acrylic acid copolymer.
[0012] Furthermore, the number average molecular weight Mn of the dispersant is between 100,000 and 1,000,000.
[0013] Furthermore, the defoaming agent is one or more of BYK-011, BYK-012, BYK-014, BYK-015, and BYK-016 from BYK of Germany.
[0014] The texturing liquid used for preparing the single crystal silicon special-shaped mesh texture structure is characterized in that it includes the texturing additive, alkaline solution and deionized water, wherein the texturing additive is 1 to 3 parts by weight, the alkaline solution is 2 to 5 parts by weight, and the deionized water is 200 to 300 parts by weight, and the alkaline texturing liquid is obtained after mixing; the alkaline solution is one or both of potassium hydroxide solution and sodium hydroxide solution.
[0015] The method for preparing the above-mentioned single crystal silicon irregular mesh texture structure is characterized in that the single crystal silicon wafer is immersed in the above-mentioned texture making liquid and the texture making is performed for 300 to 600 seconds at a temperature of 80 to 90°C.
[0016] The mechanism of the texturing additive described in the present invention is explained as follows: when one or more of polyglutamic acid, polylactic acid, sodium hyaluronate and xanthan gum are used as nucleating agents, the texturing additive is prepared into a texturing liquid with an alkaline solution and water for texturing of single crystal silicon, a large number of carboxylic acid bonds on the molecular main chain or side chain of the nucleating agent have strong adsorption to the surface of the silicon wafer, and can form hydrogen bonds with the Si-H bonds on the surface of the silicon wafer to enhance adsorption, thereby serving as a good nucleation point with good velvet-producing properties. As the reaction proceeds, the nucleation point grows into a pyramid until it covers the entire surface, making the obtained pyramid velvet surface uniform. Moreover, the polymer chain of the above-mentioned nucleating agent can also wrap the anionic surfactant and the nonionic surfactant to produce a synergistic effect, so that the surfactant can also be adsorbed on the tower surface of the formed pyramid. Under the etching of alkali, the etching speed is slow in the place where the hydrophobic chain segment is adsorbed, and the etching speed is fast in other places, resulting in micro planes with different inclination angles, thus forming a pyramid with a mesh structure on the tower surface.
[0017] The advantages and beneficial effects of the present invention are: the formula of the additive for making texturing of single crystal silicon with a special-shaped mesh structure provided by the present invention is applied to texturing of single crystal silicon, and the prepared single crystal silicon special-shaped mesh velvet structure is a randomly distributed velvet structure, and its shape is similar to that of a pyramid, so it is called a "pyramid" structure, and the tower faces of the "pyramid" structure are connected by a plurality of plane transitions with different inclination angles, the top of the tower is smooth, and the transition at the tower edge is gentle, and the tower face is also composed of many micro planes intersecting with each other, so when viewed from above, the tower face of the "pyramid" has a mesh structure with many micro planes intersecting. The size of the "pyramid" structure is uniform, the size distribution is between 1 and 4 μm, and the top of the tower is smooth and has no microstructure; it can make the velvet surface better contact with the low-temperature conductive silver paste, and improve the adhesion of the low-temperature conductive silver paste on the velvet surface. In addition, due to the increased adhesion, the low-temperature conductive silver paste has better ohmic contact with the silicon wafer, thereby reducing the width of the gate line, reducing the shading area and the amount of low-temperature conductive silver paste, and achieving the effect of reducing costs. Compared with HJT batteries with conventional velvet surfaces, the HJT batteries made of the single-crystal silicon special-shaped mesh velvet structure described in the present invention have improved opening voltage, current, and FF data, thereby achieving the goal of improving efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The suede morphology of the silicon wafer obtained in Example 1 of the present invention; Figure 2 The top morphology of the velvet structure prepared in Example 1 of the present invention is that there is no microstructure at the top of the tower and the transition is smooth.
[0019] Figure 3 This is the suede morphology of the silicon wafer obtained in Example 2 of the present invention; Figure 4 The suede morphology of the silicon wafer obtained in Example 3 of the present invention; Figure 5 This is the suede morphology of the silicon wafer obtained in Comparative Example 1 of the present invention; Figure 6 This is the morphology of the velvet structure spire prepared in Comparative Example 1, and there is a microstructure at the top of the spire. DETAILED DESCRIPTION
[0020] The present invention is further explained below through the description of specific implementation methods, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic concept of the present invention, but as long as they do not deviate from the basic concept of the present invention, they are all within the scope of the present invention. In the present invention, the preparation method of the texturing agent is not particularly limited, and the operation method familiar to those skilled in the art can be adopted. The present invention does not limit the substances in the texturing agent formula to a specific brand. For the following examples where specific conditions are not specified, they are all carried out under normal conditions, and the reagents used where the manufacturer is not specified are all conventional products that can be purchased commercially. Example 1
[0021] The texturing additive used for preparing the single crystal silicon special-shaped mesh velvet structure in this embodiment includes the following components in parts by weight: 0.3 parts of anionic surfactant sodium α-olefin sulfonate, 0.5 parts of non-ionic surfactant Tween 60, 1 part of Tremella polysaccharide, 0.7 parts of nucleating agent polyglutamic acid, 0.9 parts of dispersant sodium polyacrylate, 1 part of sodium hydroxide, 0.1 parts of degassing agent BYK-011, and 60 parts of deionized water.
[0022] Mix 1 part by weight of the above-mentioned texturing additive with 2 parts by weight of sodium hydroxide solution and 200 parts by weight of deionized water to obtain an alkaline texturing solution. The concentration of the sodium hydroxide solution is 48%. Immerse the single crystal silicon wafer in the alkaline texturing solution and texturize it at 82°C for 360 seconds to obtain a single crystal silicon irregular mesh velvet surface. The microscopic morphology of the velvet surface is as follows: Figure 1 , Figure 2 As shown, the single crystal silicon special-shaped mesh velvet structure is a randomly distributed pyramid-like "pyramid" structure, the ridges of the "pyramid" structure are connected by a plurality of planes with different inclination angles, the transition at the ridges is gentle, the top of the tower is smooth and has no microstructure, and the tower surface is composed of many micro planes. When viewed from above, the boundary lines between the micro planes form a mesh structure. Example 2
[0023] In this embodiment, the texturing additive used to prepare the single-crystal silicon special-shaped mesh velvet structure includes the following components in parts by weight: 0.4 parts of anionic surfactant sodium succinate sulfonate, 0.5 parts of nonionic surfactant Tween 80, 1 part of lentinan, 0.5 parts of nucleating agent sodium hyaluronate, 0.5 parts of dispersant polydimethyldiallyl ammonium chloride (PDMDAAC), 1.5 parts of sodium hydroxide, 0.3 parts of defoaming agent BYK-012, and 66 parts of deionized water.
[0024] 1.5 parts by weight of the above-mentioned texturing additive is mixed with 2 parts by weight of sodium hydroxide solution and 230 parts by weight of deionized water to obtain an alkaline texturing solution. The concentration of potassium hydroxide solution is 45%. The single crystal silicon wafer is immersed in the alkaline texturing solution and texturized at 86°C for 400 seconds to obtain the following: Figure 3 The suede morphology of the silicon wafer is the same as the special-shaped mesh suede structure obtained in the embodiment, with a gentle transition at the ridges and a smooth and rounded top without microstructure. Example 3
[0025] In this embodiment, the texturing additive used to prepare the single-crystal silicon special-shaped mesh velvet structure includes the following components in parts by weight: 0.3 parts of anionic surfactant α-sulfonic fatty acid methyl ester (mono) sodium salt (MES), 5 parts of non-ionic surfactant alkylphenol polyoxyethylene ether (APEO), 0.8 parts of seaweed polysaccharide, 1 part of nucleating agent polylactic acid, 0.4 parts of dispersant maleic anhydride-acrylic acid copolymer, 1.6 parts of sodium hydroxide, 0.5 parts of degassing agent BYK-014, and 70 parts of deionized water.
[0026] Mix 2 parts by weight of the above-mentioned texturing additive with 5 parts by weight of sodium hydroxide solution and 300 parts by weight of deionized water to obtain an alkaline texturing solution. The concentration of the sodium hydroxide solution is 48%. The single crystal silicon wafer is immersed in the alkaline texturing solution and texturing is performed at 84°C for 480 seconds to obtain the following: Figure 4 The velvet morphology of the silicon wafer is the same as the special-shaped mesh velvet structure obtained in the embodiment, the transition at the tower edge is gentle, and the tower top is smooth and has no microstructure and is round. Comparative Example 1
[0027] Take a conventional commercially available texturing additive (Changzhou Shichuang Energy Co., Ltd., model TS55V42) as a comparative example. According to the same application method as in Example 3, 2 parts of TS55V42 texturing additive are mixed with 5 parts of sodium hydroxide solution and 300 parts of deionized water to obtain an alkaline texturing solution. The concentration of the sodium hydroxide solution is 48%. The monocrystalline silicon wafer is immersed in the alkaline texturing solution for texturing. The texturing temperature is 84°C and the texturing time is 480s. The following is obtained: Figure 5 , 6 The velvet morphology of the silicon wafer. The structure is a traditional pyramid structure with clear edges, a flat tower surface, and a two-dimensional linear microstructure extending upward at the top of the tower.
[0028] The single crystal silicon textured structures prepared in Example 3 of the present invention and Comparative Example 1 were made into photovoltaic cells according to the same process, and the comparison of their Eta, Uoc, Isc, FF and yield is shown in Table 1.
[0029] Table 1 Photovoltaic cell performance comparison Eta Uoc (mV) Isc(mA) FF(%) Yield (%) Example 3 25.949 733.2 13.828 84.50 96.68 Comparative Example 1 25.801 730.3 13.825 84.36 96.34 The photovoltaic cell made of the single crystal silicon shaped mesh velvet structure prepared in Example 3 of the present invention has a photoelectric conversion efficiency of 0.148% higher, and the three data of the opening voltage, current, and FF are all improved, achieving the goal of improving efficiency. And because the velvet structure of Example 3 can better contact with the low-temperature conductive silver paste, the adhesion of the low-temperature conductive silver paste on the velvet surface is improved, and the defect of broken gate is reduced, so the yield rate is also improved.
Claims
1. A single crystal silicon irregular mesh velvet structure, characterized in that: It comprises randomly distributed "pyramid" structures with a size of 1 to 4 μm; the top of the "pyramid" structure is smooth, the side of the "pyramid" is transitioned to the top by multiple ridges with different inclination angles, and the ridges are transitioned by multiple planes with different inclination angles; the tower surface is composed of multiple micro-planes intersecting with each other, and when the "pyramid" structure is viewed from above, the tower surface of the "pyramid" has a mesh structure of micro-planes intersecting in a mesh shape.
2. A texturing additive for preparing the single crystal silicon special-shaped mesh texture structure according to claim 1, characterized in that: The invention comprises the following components calculated by weight: 0.1-1 parts of anionic surfactant, 0.1-5 parts of nonionic surfactant, 0.05-1 parts of plant polysaccharide compound, 0.1-5 parts of nucleating agent, 0.1-2 parts of dispersant, 1-2 parts of sodium hydroxide, 0.1-1 parts of defoaming agent and 60-80 parts of deionized water.
3. The texturing additive according to claim 2, characterized in that: The anionic surfactant is one or more of linear alkylbenzene sulfonate (LAS), α-olefin sulfonate (AOS), alkyl sulfonate (SAS), succinate sulfonate, and α-sulfonated fatty acid methyl ester (mono) sodium salt (MES).
4. The texturing additive according to claim 2, characterized in that: The nonionic surfactant is one or more of fatty alcohol polyoxyethylene ether (AEO), fatty acid polyoxyethylene ester, alkylphenol polyoxyethylene ether (APEO), Tween 60, and Tween 80.
5. The texturing additive according to claim 2, characterized in that: The plant polysaccharide compounds are one or more of Tremella polysaccharide, Lentinan, β-glucan, seaweed polysaccharide, carrageenan and konjac glucomannan.
6. The texturing additive according to claim 2, characterized in that: The nucleating agent is one or more of polyglutamic acid, polylactic acid, sodium hyaluronate and xanthan gum.
7. The texturing additive according to claim 2, characterized in that: The dispersant is one or more of sodium polyacrylate, ammonium polyacrylate, polydimethyldiallylammonium chloride (PDMDAAC), and maleic anhydride-acrylic acid copolymer.
8. The texturing additive according to claim 2, characterized in that: The number average molecular weight Mn of the dispersant is between 100,000 and 1,000,000.
9. The texturing liquid for preparing the single crystal silicon irregular mesh texture structure according to claim 1, characterized in that: It comprises the texturing additive, alkaline solution and deionized water as described in any one of claims 2 to 8, wherein the texturing additive is 1 to 3 parts by weight, the alkaline solution is 2 to 5 parts by weight, and the deionized water is 200 to 300 parts by weight, and an alkaline texturing liquid is obtained after mixing; the alkaline solution is one or both of potassium hydroxide solution and sodium hydroxide solution.
10. A method for preparing the single crystal silicon irregular mesh velvet structure according to claim 1, characterized in that: The monocrystalline silicon wafer is immersed in the texturing solution as claimed in claim 9, and the texturing is performed for 300 to 600 seconds at a temperature of 80 to 90°C.
Citation Information
Cited By
Textured structure of combined passivation back contact battery and preparation method of textured structure
CN119789617A